TRADISI DAN SIMBOL YANG SERUPA: STUDI PERBANDINGAN PADA GAMBAR CADAS MUDA DI INDO-MALAYSIA - Leihitu, Irsyad (Penerbit BRIN (BRIN Publishing), 2020)
Abstract, The Similarity of Traditions and Symbols: Comparative Study of Recent Rock Art in Indo-Malaysia. As an ancient art, rock art, in general, is always associated with the prehistoric hunter-gatherer communities in the upper Paleolithic period or about 40,000 years ago. However, it was later discovered that the tradition of drawing/painting inside the cave was still practiced by modern hunter-gatherer communities in the 19th century, especially in the Indo-Malaysian region. This article seeks to conduct a comparative study of